The importance of inventory sanitation processes in public entities (2019)
To achieve the efficient administration of inventories in a public entity, it is necessary to identify, classify, and enter the different elements. The general storekeeper within its management, classifies the goods according to their nature and the own policies of each entity to determine: their character, either devolutive / controllable or of consumption.